2019
DOI: 10.5334/aogh.2403
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Environmental Health in South and Southeast Asia: Networking for Better Child Health Outcomes

Abstract: Children are particularly vulnerable to environmental hazards because they receive higher doses of pollutants in any given environment and often do not have equitable access to social protection mechanisms such as environmental and health care services. The World Health Organization established a global network of collaborating centres that address children’s environmental health (CEH). The network developed a focus on low- and middle-income countries (LMICs) and is broadening its reach by conducting regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…prenatal, infancy) is especially worrying [4,14]. Exposure to pesticides, heavy metals and industrial chemicals are problematic for numerous children at different parts of the globe [15,16]. A report on seven countries from South and southeast Asia has indicated that outdoor and household air pollution is the more common environmental health problem for children, and whose solutions are not immediately apparent or easily implementable [16].…”
Section: Environmental Concerns and Search For Nutraceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…prenatal, infancy) is especially worrying [4,14]. Exposure to pesticides, heavy metals and industrial chemicals are problematic for numerous children at different parts of the globe [15,16]. A report on seven countries from South and southeast Asia has indicated that outdoor and household air pollution is the more common environmental health problem for children, and whose solutions are not immediately apparent or easily implementable [16].…”
Section: Environmental Concerns and Search For Nutraceuticalsmentioning
confidence: 99%
“…For instance, exposure to arsenic in the uterus induced alterations in DNA methylation in the newborn liver that were related to cancer development later in life [14]. Infants born to mothers exposed to arsenic showed increased expression of inflammatory and DNA damage markers and the follow-up of these children indicated impairment of oxidative DNA repair [16,17].…”
Section: Environmental Concerns and Search For Nutraceuticalsmentioning
confidence: 99%
“…Most studies reviewed were also unable to link self‐reported or observed health effects to environmental contamination from particular activities at a site because of potential confounding factors. That is, nutritional deficiencies, comorbidities, lifestyle behaviors, and socioeconomic factors have been found to affect contaminant uptake and contribute to increased vulnerability or susceptibility in LMIC populations (Caravanos et al, 2013; Falk, 2003; Kordas et al., 2018; Nweke & Sanders III, 2009; Sly et al., 2019; WHO, 1995; Xie et al., 2013). In studies of children and toddlers living in an open‐pit tin‐ore mining settlement in Rondonia, Brazil, Dórea et al.…”
Section: Key Findings Based On Literature Reviewmentioning
confidence: 99%
“…Although this includes traditional point sources, such as mining and smelting, there are a growing number of nonpoint sources located within and throughout local communities, such as used lead acid battery (ULAB) recycling, artisanal and small‐scale gold mining (ASGM), and small‐scale tanneries. Children are especially vulnerable to environmental hazards in LMICs and frequently serve as a source of labor, such as picking up waste in disposal and recycling sectors, helping to dismantle and wash used battery components, and participating in all stages of ASGM ranging from ore extraction to processing and burning (Ogola et al, 2002; Sly et al., 2019; World Health Organization [WHO], 2016, 2017). Hundreds of cases of acute lead poisonings and deaths among children have been documented in Senegal, West Africa and Zamfara State, Nigeria due to local ULAB and ASGM activities (Jones, Diop, Block, Smith‐Jones, & Smith‐Jones, 2011; Lo et al., 2012).…”
Section: Introduction: Risk Analysis In the Context Of Land‐based Pollution In Low‐ And Middle‐income Countriesmentioning
confidence: 99%
“…These vulnerabilities persist even when controlling for more traditional social determinants such as occupation, gender, age, income, and education [17,18]. Occupational risks, such as exposure to unhealthy air or lack of access to clean water and sanitation on the job, are of particular concern as they relate to some of the leading preventable causes of morbidity and mortality and are situated within the broader development context of the Southeast Asia region [19][20][21].…”
Section: Introductionmentioning
confidence: 99%